2009
DOI: 10.1097/ta.0b013e3181a60593
|View full text |Cite
|
Sign up to set email alerts
|

Standard Examination System for Laparoscopy in Penetrating Abdominal Trauma

Abstract: Standard systematic laparoscopic exploration was 100% effective to detect SBI in the peritoneal cavity. Conversion from LIT to laparotomy should be done if injuries to blind spot zones are found which are poorly evaluated by LIT. Therapeutic LIT is feasible in PAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 43 publications
4
65
0
3
Order By: Relevance
“…Approximately 30% of patients with peritoneal penetration do not have intra-abdominal injuries and screening laparoscopy may still lead to high nontherapeutic laparotomy rates (24,25). However, use of DL in a systematic standardized approach for the evaluation of intraabdominal injuries rather than as a simple screening test for peritoneal violation is reported to spare 73% of nontherapeutic laparotomies (8).…”
Section: Screening and DLmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 30% of patients with peritoneal penetration do not have intra-abdominal injuries and screening laparoscopy may still lead to high nontherapeutic laparotomy rates (24,25). However, use of DL in a systematic standardized approach for the evaluation of intraabdominal injuries rather than as a simple screening test for peritoneal violation is reported to spare 73% of nontherapeutic laparotomies (8).…”
Section: Screening and DLmentioning
confidence: 99%
“…Both animal studies and case reports suggest that the increased abdominal pressure due to pneumoperitoneum may increase intracerebral pressure and worsen an underlying TBI (15). Relative contraindications include acute lung injury, previous laparotomy, multiple system injuries, chronic cardiorespiratory disease, and third-trimester pregnancy (8,14).…”
Section: Indications Contraindications and Rationalementioning
confidence: 99%
“…Для исключения таких ошибок предлагается дополнять лапароскопию четырехсан-тиметровым разрезом, через который последова-тельно извлекают и экстракорпорально осматрива-ОБЗОРЫ ют тонкую кишку [29]. Другие, наоборот, считают, что при лапароскопии возможен осмотр всей тон-кой кишки и сообщают об отсутствии пропущенных повреждений [30]. Выявление повреждений толстой кишки иногда вызывает существенные трудности и при лапаротомии, лапароскопия в таких случаях мо-жет иметь даже некоторые преимущества перед ла-паротомией, особенно при осмотре фиксированных участков толстой кишки [30].…”
Section: повреждения полых органовunclassified
“…Другие, наоборот, считают, что при лапароскопии возможен осмотр всей тон-кой кишки и сообщают об отсутствии пропущенных повреждений [30]. Выявление повреждений толстой кишки иногда вызывает существенные трудности и при лапаротомии, лапароскопия в таких случаях мо-жет иметь даже некоторые преимущества перед ла-паротомией, особенно при осмотре фиксированных участков толстой кишки [30].…”
Section: повреждения полых органовunclassified
“…9 However, Kawahara et al reported that a systemic approach for laparoscopic abdominal examinations resulted in the complete absence of missed bowel injuries and high avoidance of unnecessary laparotomies (73.33%). 35 Nevertheless, patients with suspected retroperitoneal involvement and those with deteriorating haemodynamic parameters should undergo an open laparotomy to prevent complications secondary to a missed injury.…”
Section: Complications Of Laparoscopymentioning
confidence: 99%